2001
DOI: 10.1007/s004240000476
|View full text |Cite
|
Sign up to set email alerts
|

Swelling-activated taurine and K + transport in human cervical cancer cells: association with cell cycle progression

Abstract: The aim of this study was to investigate swelling-activated taurine and K+ transport in human cervical cancer cells under various culture conditions, testing the hypothesis that the progression of cell cycle was accompanied by differential activities of swelling-activated transport pathways. Aphidicolin, an inhibitor of deoxyribonucleic acid (DNA) synthesis, was used to synchronize the cell cycle. The distribution of cell cycle stage was determined by fluorescence-activated cell sorting (FACS). Hypotonicity ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…1-3) and accumulated cells at G 0 /G 1 phase (Fig. 5); this finding is consistent with recent observations in cancer cells and fibroblasts (6,34,45). Our results demonstrated that this effect is related to the downregulation of the cell cycle regulatory proteins cyclin D1 and cyclin E (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…1-3) and accumulated cells at G 0 /G 1 phase (Fig. 5); this finding is consistent with recent observations in cancer cells and fibroblasts (6,34,45). Our results demonstrated that this effect is related to the downregulation of the cell cycle regulatory proteins cyclin D1 and cyclin E (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Phosphorylation of p38 MAPK following hyperosmotic stress has been shown in several cell types, such as fibroblasts (23), human cervical cells (36), and human articular chondrocytes (41,42). In agreement with these studies, we have shown an elevation of p38 MAPK phosphorylation following hyperosmotic stress at early phases of the exposure.…”
Section: Discussionsupporting
confidence: 90%
“…The role of the ERK1/2 pathway in RVD has not been delineated; however, indirect activation of ERK1/2 via the Ras-Raf-MEK pathway has been suggested in hepatocytes (8). Other studies have linked activation of ERK1/2 to activation of the Cl Ϫ channel in corneal epithelial cells (19) and astrocytes (6) and to activation of the K ϩ channel in cervical cancer cells (36). Although Cl Ϫ and K ϩ play an important role in volume regulation following cell swelling in response to hypo-osmotic stress and elevation of intracellular Ca 2ϩ (18), the current study suggests a link between ERK1/2 phosphorylation and TRPV4 channel expression, where ERK1/2 phosphorylation regulates endogenous TRPV4 channel expression.…”
Section: Discussionmentioning
confidence: 99%
“…[22,38,43,90,92,[101][102][103]. As discussed above, inhibition by either compound is commonly cited as evidence for taurine transport via volume-activated anion channels.…”
Section: Inhibition Of Volume-sensitive Taurine Efflux By Dids and Tamentioning
confidence: 99%